Epidemiological study of p16 incidence in head and neck squamous cell carcinoma 2005- 2015 in a representative Northern European population - Mylly, Mari (My University, 2023)
Human papillomavirus (HPV) infection is a known risk factor for developing head and neck squamous cell carcinoma (HNSCC) especially in oropharyngeal region and the incidence of these cancers have increased globally. Determining HPV status is important as survival and response for treatments are dependent on HPV expression. p16 immunohistochemistry is widely used method to detect HPV positivity in cancer. The aim of this study was to study amendment of HNSCC incidence in representative Northern European population and utility of HPV surrogate marker p16 in clinical decision-making. All new 1033 HNSCC patients diagnosed and treated in Southwest Finland regional referral centre of Turku University Hospital in 2005-2015 were identified and analyzed. The incidence of p16 positivity in HNSCC and oropharyngeal squamous cell carcinoma (OPSCC) increased in Southwest Finland area during the follow-up. p16 positivity involved a high locoregional correlation, as 72% of all p16 positive tumors located in oropharynx and more than 80% of tumors from other sites were p16 negative. In OPSCCs p16 positivity was proved to be a significant factor for improved survival. p16 positive OPSCC patients had better prognosis regardless of treatment modality. All HNSCC patients benefited from combining chemotherapy with radio-therapy, regardless of p16 expression. Study reaffirms that p16 expression offers a prognostic biomarker in OPSCC and could potentially be used cancer treatment stratification. Focusing of p16 testing for only OPSCC might be most costeffective in clinical practice.
Keywords: HNSCC, OPSCC, HPV, p16